Implementation of a photovoltaic system for make the most of solar energy during the summer months in the San Borja - Rivera Tito, Harry A. (2022)
Through this work we explain a method to provide electrical power to a group of people living in the district of San Borja - Lima, through a PV system, which is not common in the area. This would help to reduce emission levels of carbon dioxide (CO2) to the atmosphere. It has been determined by the Solar Atlas of Peru that the coast region solar power reaches 6 to 6,5 kW.h/m2 per day, average in the month of March, if we convert this data to energy is equivalent to 21,6 to 23,4 MJ/m2, which is of great advantage for the proyect.